International public television: a comparative analysis between Brazil and Portugal - Napolitano, Carlo Jose [UNESP]; Silva Santos, Augusto Junior da [UNESP] (Univ Federal Sergipe, 2017)
The aim of this article is to identify the characteristics of Brazil's (Brasil Internacional) and Portugal's (RTPi) public televisions with international reach by means of a comparative analysis based on three aspects: objectives of the channels; management models; funding models. In light of the theoretical and documental background as well as of the outcomes of the analysis, it was possible to verify that the international public service of communication provided by Portugal is guided by legal and contractual rules. On the other hand, Brazil does not rely on juridical norms in order to regulate the existence and the operation of a public TV channel broadcast internationally, which might weaken the performance of this service.
Keywords: public television; international television; TV Brasil Internacional; RTPi